An unusual case of Epstein–Barr virus driven lymphoproliferative disorder of the conjunctiva which mimicked a high grade lymphoma: a sheep in wolf's clothing. Issue 7 (26th June 2009) - Powari, M; Simpson, A; Quinn, A; McCullagh, P; Sarsfield, P
Abstract : Lymphoid proliferations represent 25–33% of acquired sub-epithelial conjunctival lesions which are excised or biopsied in patients over 15 years of age. These lesions are reported in association with Epstein–Barr virus (EBV). One such case of EBV associated spontaneously regressed monoclonal B cell infiltrate in conjunctiva that mimicked a large B cell lymphoma is reported.